A Critical Analysis of Debates Around Mental Health Calls in the Prehospital Setting. (28th April 2017) - Ford-Jones, Polly Christine; Chaufan, Claudia
Paramedics, health care workers who assess and manage health concerns in the prehospital setting, are increasingly providing psychosocial care in response to a rise in mental health call volume. Observers have construed this fact as "misuse" of paramedic services, and proposed as solutions better triaging of patients, better mental health training of paramedics, and a greater number of community mental health services. In this commentary, we argue that despite the ostensibly well-intentioned nature of these solutions, they shift attention and accountability away from relevant public policies, as well as from broader economic, social, and political determinants of mental health, while placing responsibility on those requiring services or, at best, on the health care system. We also argue that the perspective of paramedics, who are exposed to, and interact with, individuals in their everyday environments, has the potential to inform a better, structural and critical, understanding of the factors driving the rise in psychosocial crises in the first place. Finally, we suggest that a greater engagement with the political and social determinants of mental health would lead to preventing, rather than primarily reacting to, these crises after the fact.